141k views
4 votes
Combinatorics: what is the coefficient of (a^2)(b^3)(c) in (2a - b + 3c)^6?

User Dave Moore
by
5.2k points

1 Answer

6 votes

Answer:

The coefficient of a²b³c is -720

Explanation:

Given:
(2a-b+3c)^6

Let 2a-b = x and 3c = y


(x+y)^6

General term of binomial expansion.


  • T_(r+1)=^nC_rx^(n-r)y^r

where, n=6 , r=1 ( because exponent of c is 1)


\Rightarrow ^6C_1x^(6-1)y^1


\Rightarrow 6(2a-b)^(5)3c
\because y=3c, x=2a-b


\Rightarrow 18(2a-b)^(5)c ----------(1)

Now, we simplify (2a-b)⁵


T_(r+1)=^5C_r(2a)^(5-r)(-b)^r

The exponent of b is 3 and a is 2 .

If we take r=3 will get exponent of b is 3 and a is 2

So, put r=3


T_(4)=^5C_3(2a)^(2)(-b)^3=-40a^2b^3

Substitute into equation (1)


\Rightarrow 18\cdot -40a^2b^3c


\Rightarrow -720a^2b^3c

Hence, The coefficient of a²b³c is -720

User GGberry
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.